STUDI KANDUNGAN MINYAK DAN STRUKTUR KOMUNITAS MAKROZOOBENTHOS DI PERAIRAN SEKITAR BUANGAN LIMBAH CAIR KILANG MINYAK PERTAMINA UP II DUMAI - Nurrachmi, Irvina; Amin, Bintal (Jurnal Perikanan dan Kelautan, 2007)
Study on the effects of oil content on the macrozoobenthic community in thecoastal waters receiving oil refinery effluents has been conducted. Samples ofwater and sediment were collected in August 2006 from three stations in oilrefinery and one control station in far distance from the oil refinery area. Waterquality parameters measured in the present study were still in the tolerable levelfor the aquatic biota. Oil content in the stations close to the oil refinery (10.17 -12.17 ppm and 11.17 - 15.42 ppm) was higher than the control station (6.92 and6.17 ppm) at high and low tide respectively. The abundance of macrozoobenthicat the control station (333.23 id/m2) was higher that the oil refinery (151.50 -281.25 ind/m2). Simple linear regression showed that macrozoobenthic abundancewas negatively correlated with oil content in the water column (Y = 431.92 -17.81 X; r = 0.64) and it was positively correlated with total organic matter in thesediment (V = -174.55 + 27.23X: r = 0.69). This study showed that the oil refineryand its related activities have significant contribution to the elevated oil contentand the decreasing water quality which finally affect the macrozoobenthiccommunity structure in the surrounding aquatic environments.